Kejadian Kasus Pneumonia Pada Pasien Anak Dengan Covid-19 Yang Dirawat Di Ruang Isolasi RSUD Dr. Raden Soedjono - MN Alpi Apriansah (Unram Medical Journal, 2022)
Background: The number of Covid-19 cases continues to increase. Patients with Covid-19 show variousclinical signs and symptoms, a small number of cases can progress to lower respiratory tract infections in the form of pneumonia and rapidly worsen into respiratory failure. Methods: This research is a retrospective descriptive study. Data were obtained from the medical records of pediatric patients who were confirmed positive for Covid-19 and diagnosed with pneumonia in the pediatric isolation room of RSUD Dr. Raden Soedjono Selong from May 2020 to March 2021 Results: There was 55 child confirmed positive for Covid-19, consisting of 32 boys and 23 girls. The number of children who were confirmed positive for Covid-19 with pneumonia was 16 people, of which 2 children had other comorbid diseases. The most common symptom that patients complain about is fever. Most of the patients who were confirmed positive for Covid-19 with pneumonia treated in the isolation room were female, with the highest age range being between the ages of 1 month to 2 years and over 2 years to 5 years. The radiological appearance of the patient is mostly typical of pneumonia.